Effect of pregnant women’s knowledge and therapy regimentation towards compliance in consuming iron (Fe) tablets and anemia degree in South Kediri Public Health Center year 2016 - Dina Dewi Anggraini; Windhu Purnomo; Bambang Trijanto (Universitas Airlangga, 2016)
Objectives: This study aimed to analyze the influence of knowledge and regimentation of pregnant women consume tablets therapy adherence iron (Fe) and anemia in pregnant women in the South Regional Health Center Kediri.Materials and Methods: This study used observational analytic with cross sectional design. The population consisted of 63 third trimester pregnant women and samples taken were 34 third trimester pregnant women who have received 90 tablets of iron (Fe), with a simple random sampling technique. Data obtained from questionnaires, books Maternal and Child Health, and in-depth interviews. Data analysis was performed using ordinal regression and logistic regression.Results: There was an effect of knowledge of pregnant women on adherence to consume tablets of iron (Fe), there is no influence regimentation of therapy on adherence to consume tablets of iron (Fe), and no effect of compliance sufficient to consume tablets of iron (Fe) against anemia in pregnant women (p=0.012). Conclusion: The higher the level of knowledge possessed by pregnant women, pregnant women, the more it tends to stick to consume tablets of iron (Fe) during pregnancy. And no regimentation of therapeutic effect on adherence to consume tablets of iron (Fe) in pregnant women.